Remaking Gender and the Family Perspectives on Contemporary Chinese-language Film Remakes - Woodland, Sarah (Women and Gender in China Studies, 2018)
In Remaking Gender and the Family, Sarah Woodland examines the complexities of Chinese-language cinematic remakes, exploring how source texts are reshaped for their new audiences, and focusing on how changes in representations of gender connect with perceived socio-cultural, political and cinematic values within China.; Readership: This monograph would be of relevance to academics and non-specialists with an interest in Asian/Chinese-language cinema, gender, film, culture and remake studies. The work be a useful addition to institutional collections on these topics as well.